Applying the ethical framework for donation after circulatory death to thoracic normothermic regional perfusion procedures. Issue 5 (28th January 2022) - Wall, Anji E.; Fiedler, Amy; Karp, Seth; Shah, Ashish; Testa, Giuliano
Abstract : The novel approach of thoracic normothermic regional perfusion (TA‐NRP) for in‐situ preservation of organs prior to removal presents a new series of ethical questions about donation after circulatory determination of death (DCD) procedures. This manuscript describes the framework used for the analysis of ethical acceptability of DCD donation and analyzes the specific practice of TA‐NRP DCD within that framework to demonstrate that TA‐NRP DCD can be performed within the ethical boundaries of DCD donation. We argue that TA‐NRP DCD organ procurements meet the ethical standards of informed consent, non‐maleficence, adherence to the dead donor rule, and irreversibility, and as such, are ethically acceptable. We also describe the potential benefits of TA‐NRP DCD procedures that result from higher organ yields and better recipient outcomes. Finally, we call for open and transparent support of TA‐NRP DCD by professional organizations as a necessary cornerstone for the advancement of TA‐NRP DCD procedures. Abstract : The authors describe the ethical framework for analysis of donation after circulatory death, apply it to the normothermic regional perfusion technique for donation after circulatory death, and address ethical concerns with the normothermic regional perfusion technique. See related article by Parent et al on page 1307 and editorial by Glazier and Capron on page 1289